Factors Affecting The Appearance of Diabetic Wounds In Patients With Diabetes Mellitus at The Bireun Regional Hospital Polyclinic - Erna Masdiana; Tua Parlindungan (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2022)
Diabetes, where there are blackened wounds from the layers of the skin to the dermis layer and tissue death occurs. The aim of the study was to obtain an overview of the factors that influence the occurrence of wounds in type 2 diabetes patients Gangrene wound or, this wound is a complication caused by someone who has at the Bireuen. The number of respondents in this research amounted to 50 people. Diabetic sufferers who experience injuries, carried out on March 20 to March 25, 2021 with a sampling technique that is accidental sampling. This study shows a risk factor for age 40 years with an OR value of 15.190 and a P-value of 0.000, a risk factor for long suffering from DM â‰¥ 8 years with an OR value of 8.486 and p = 0.003, a risk factor for a history of diabetic ulcers with an OR value of 9.667. and p = 0.004, the risk factor for lack of foot care with an OR value = 4.500 and p = 0.042, a smoking risk factor with an OR value = 0.371 and p = 0.334, an exercise history factor with an OR value = 8.486 and p = 0.003, family support factor with OR = 1.781 and p = 0.501 which means the variable age 40 years, duration of suffering from DM 8 years. The results of this study can provide information to nurses so as to reduce the incidence of injuries in diabetic patients.